One visit endodontic on asymtomatic mummificated mandibular molar - Sholeh Ardjanggi; Dian Agustin Wahjuningrum; Tamara Yuanita; Eric Priyo Prasetyo (Universitas Airlangga, 2020)
Background. The main goal of root canal treatment is the prevention or treatment of apical periodontitis, which leads to the preservation of natural teeth. Traditionally, root canal treatment is carried out in a number of visits, using extra disinfecting agents in addition to irrigant used during cleaning and shaping procedures that primarily aim to reduce or eliminate microorganisms and their byproducts. from the root canal system before it is obtained. Recent advances in Endodontic technology, attracting dental experts and endodontists to perform root canal treatment in one visit. Numerous studies evaluate the effectiveness of single-versus multiple-appointment root canal treatment have been published, which reported no significant differences in effectiveness (healing rates) between these two treatment regimens.Purpose : preservation of the integrity of the molar teeth that have symptomatic complaints by taking proper care with a short visit time. Caset: A 21-year-old woman presents with concern in her lower left tooth, the patient tells that the tooth had been treated before at the dentist when she was a child. On clinical examination there is a composite restoration in occlusal tooth # 36, non vital teeth. On periapical radiology there are radiopaque on pulp chamber and a diffuse radiolucent area in the apical area of tooth # 36, then the diagnosis then determined Previously initiated therapy with asymptomatic apical periodontitis. Case Management : Tooth # 36 treated with one visit root canal treatment, Treatment is continued with fiber post installation and crown, patients no longer complain of pain after treatment. Teeth function normally again. Conclusion: One visit root canal treatment can successfully eliminate patient complaints and restore tooth function.